Airborne dissemination of Burkholderia (Pseudomonas) cepacia from adult patients with cystic fibrosis. - Humphreys, H. (1994)
BACKGROUND--Burkholderia (Pseudomonas) cepacia is an increasingly important pathogen in patients with cystic fibrosis but it is unclear how it spreads from patient to patient. A study was undertaken to determine whether B cepacia could be recovered from room air occupied by colonised adult patients with cystic fibrosis. METHODS--Air samples were obtained consecutively from an enclosed room or isolation cubicle before, during, and after occupation by six patients on nine occasions using a surface air sampler incorporating contact plates with selective medium. Settle plates were also used and sputum from five patients was cultured. RESULTS--B cepacia was recovered from room air during occupation by five of six patients, the number of bacteria ranging from 1 to 158 cfu/m3 (mean 32 cfu/m3). The number of bacteria isolated was greater when patients were coughing. B cepacia persisted in room air on four occasions after the patient left the room, on one occasion for up to 45 minutes. CONCLUSIONS--The isolation of B cepacia from the air of rooms occupied by colonised patients suggests that dissemination might occur by aerosol as well as by direct physical contact with patients or contaminated environmental sites.